Accountability and Transparency of Wakf in the Management of Social Funds and Empowerment of the People - Ningsih, Fajri Mulia; Yulianto, Januari Gilar; Muarrifah, Safrina (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
As an instrument of Islamic philanthropy with a rich history, Waqf has great potential in improving the management of social funds and empowering the community. This research examines the crucial role of accountability and transparency in managing social funds and empowering the people through waqf institutions. The analysis focuses on how implementing these principles can strengthen the effectiveness of waqf fund management to achieve humanitarian goals and community empowerment.The research methodology includes a literature review and case study. The research results show that the use of relevant accounting standards, transparency in financial reporting, and strong accountability in waqf management institutions positively influence the management of social funds. Hopefully, this conclusion will provide further insight into optimizing the management of social funds through the principles of accountability and transparency in the realm of waqf.The author's suggestion for further research is to adopt a quantitative approach through interviews or questionnaires focusing on specific nazir entities. The research results will likely provide significant practical contributions to the Nazir entity by exploring in-depth case studies.